The Impact of Applying Islamic Murabaha in Libyan Commercial Banks on Profitability Rates: An Applied Study at Al-Jumhouria Bank (Comprehensive Journal of Science, 2026)
This study aims to demonstrate the impact of Murabaha financing on the profitability of banks operating in Libya. To achieve this objective, the study examined profitability indicators, namely Return on Assets (ROA) and Return on Equity (ROE), at Al-Jumhouria Bank for the years 2013-2024. The study employed a descriptive methodology and statistical analysis to determine the statistically significant impact of Murabaha financing on Al-Jumhouria Bank's profitability.One of the key findings of the study is that Murabaha financing has a positive, but not statistically significant, impact on the ROA and ROE of Al-Jumhouria Bank during the study period.